PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E TERHADAP PENGUASAAN KONSEP SISTEM PEREDARAN DARAH MANUSIA KELAS VIII SMP NEGERI 19 PALEMBANG - Choirunniswah Choirunniswah; Dini Afriansyah; Titin Veronika (Bioilmi: Jurnal Pendidikan, 2017)
This study aims to determine the effect of Learning Cycle 5E learning model on the mastery ofthe concept of human circulatory system. This research was conducted at State Junior HighSchool 19 Palembang on January 04 until February 19, 2017. The research method used in thisresearch is a quasi experiment with Noquivalent Control Group Design research design.Population in this study all students of class VIII SMP Negeri 19 Palembang consisting of 8classes, amounting to 298 students. Sampling was used by using purvosive sampling technique.The sample of this study class VIII.7 as the experiment amounted to 38 and class VIII.8 as acontrol class amounted to 35 students. In the learning process, experimental class is taught byusing Learning Cycle 5E model and control class is taught with Direct Intruction model. Dataretrieval uses conception master test with open multiple choice form which has been tested forits validity and reliability. The results of this study indicate that the average N-gain of theexperimental class is 0.69 which belongs to the medium category and the average N-gain forthe control class is 0.30 which belongs to the low category. Data analysis using t-test withsignificant level 0,05 obtained tcount = 6,568 while ttabel = 1,669 seen that tcount. Therefore(Ha) accepted and (H0) rejected thus can be concluded that there is a significant influence onLearning Cycle 5E learning model on the mastery of the concept of circulation system ofhuman class VIII SMP Negeri 19 Palembang